Long-term use of everolimus for refractory arrhythmia in a child with tuberous sclerosis complex - Sandmann, Christoph; Syrbe, Steffen; Hebe, Joachim; Kreft, Jannis; Stark, Sebastian; Milde, Till; Völkers, Mirko; Hoffmann, Georg F.; Gorenflo, Matthias; Kovacevic, Alexander (American journal of medical genetics, 2024)
Tuberous sclerosis complex is associated with the occurrence of cardiac rhabdomyomas that may result in life-threatening arrhythmia unresponsive to standard antiarrhythmic therapy. We report the case of an infant with multiple cardiac rhabdomyomas who developed severe refractory supraventricular tachycardia (SVT) that was successfully treated with everolimus. Pharmacological mTOR inhibition rapidly improved arrhythmia within few weeks after treatment initiation and correlated with a reduction in tumor size. Intermediate attempts to discontinue everolimus resulted in rhabdomyoma size rebound and recurrence of arrhythmic episodes, which resolved on resumption of therapy. While everolimus treatment led to successful control of arrhythmia in the first years of life, episodes of SVT reoccurred at the age of 6 years. Electrophysiologic testing confirmed an accessory pathway that was successfully ablated, resulting in freedom of arrhythmic events. In summary we present an in-depth evaluation of the long-term use of everolimus in a child with TSC-associated SVT, including the correlation between drug use and arrhythmia outcome. This case report provides important information on the safety and efficacy of an mTOR inhibitor for the treatment of a potentially life-threatening cardiac disease manifestation in TSC for which the optimal treatment strategy is still not well established.